Foto van collage over de USSR: "Wij kennen noch crisis noch werkloosheid! Wij bouwen het socialisme" - Vooren, P.H.,
Foto van collage over de USSR: "Wij kennen noch crisis noch werkloosheid! Wij bouwen het socialisme".